A Double Child Coffin from the Southern Crypt of the Holy Trinity Church in Radzyń Podlaski (19th Century) - Dabralet, Igor; Michalik, Jakub; Grupa, Małgorzata; Gałka, Barbara (Analecta Archaeologica Ressoviensia, 2022)
The lives of children in the past were both ephemeral and fragile. The birth of a child, although expected and prayed for, was inevitably connected with the fear of death of both the mother and child, and every childbirth was a kind of a challenge. Unfortunately, in many cases, it finished with death during the delivery or just after. Surviving childhood safely was a constant struggle for the smaller members of a community. This information is evidenced during archaeological explorations of churches and burial grounds. No matter whether they were rich or poor, death took its toll on every social group. There was only the difference in the way of burial ceremony and accessories attributed to it. Some of the child burials were comparable with the richest burials of adults. One of them, a burial in a double coffin, attracted archaeologists’ attention at the very beginning of exploration in Radzyń Podlaski. A child burial in a double coffin can be classified as a unique find, not only in the area of Poland but also in Europe.